Streptococcus pneumoniae Evades Host Cell Phagocytosis and Limits Host Mortality Through Its Cell Wall Anchoring Protein PfbA - Yamaguchi, Masaya; Hirose, Yujiro; Takemura, Moe; Ono, Masayuki; Sumitomo, Tomoko; Nakata, Masanobu; Terao, Yutaka; Kawabata, Shigetada (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcus pneumoniae is a Gram-positive bacterium belonging to the oral streptococcus species, mitis group. This pathogen is a leading cause of community-acquired pneumonia, which often evades host immunity and causes systemic diseases, such as sepsis and meningitis. Previously, we reported that PfbA is a β-helical cell surface protein contributing to pneumococcal adhesion to and invasion of human epithelial cells in addition to its survival in blood. In the present study, we investigated the role of PfbA in pneumococcal pathogenesis. Phylogenetic analysis indicated that the pfbA gene is highly conserved in S. pneumoniae and Streptococcus pseudopneumoniae within the mitis group. Our in vitro assays showed that PfbA inhibits neutrophil phagocytosis, leading to pneumococcal survival. We found that PfbA activates NF-κB through TLR2, but not TLR4. In addition, TLR2/4 inhibitor peptide treatment of neutrophils enhanced the survival of the S. pneumoniae ∆pfbA strain as compared to a control peptide treatment, whereas the treatment did not affect survival of a wild-type strain. In a mouse pneumonia model, the host mortality and level of TNF-α in bronchoalveolar lavage fluid were comparable between wild-type and ∆pfbA-infected mice, while deletion of pfbA decreased the bacterial burden in bronchoalveolar lavage fluid. In a mouse sepsis model, the ∆pfbA strain demonstrated significantly increased host mortality and TNF-α levels in plasma, but showed reduced bacterial burden in lung and liver. These results indicate that PfbA may contribute to the success of S. pneumoniae species by inhibiting host cell phagocytosis, excess inflammation, and mortality by interacting with TLR2.